Administrasi Sekolah, Unsur-unsur Administrasi dan Bidang Garapan Administrasi Sekolah - Salwa Aulia Syarief; Nurhayati Nurhayati (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
The role of school administration is very important in carrying out the basic functions of Islamic educational institutions. School administration as the center for managing teaching and learning activities also covers various fields ranging from resource management, financial management, to planning and implementing academic policies. This research aims to identify the role of school administration in improving the operational effectiveness and quality of Islamic education. The method used in this research is library research, which aims to collect, analyze and compile information from various literary sources in order to obtain a comprehensive understanding of the topic being researched. The data analysis technique used is descriptive-qualitative, with the aim of describing and interpreting information obtained from the literature. This research shows that the role of school administration is very important in improving the operational effectiveness and quality of Islamic education. Good administration includes technical management, creating an environment that supports the moral and spiritual development of students. With effective implementation, it is hoped that schools will be able to provide Islamic education that is not only of academic quality, but can also shape students' character in accordance with Islamic values. It is hoped that this research can become a reference for policy makers and Islamic education practitioners in formulating better management strategies, so as to improve the overall quality of Islamic education.